Relationship between knowledge and parity with parental participation in child developmental screening - Titin Novayanti Dey; Putu Eva Yuni Dyantari; Luh Yenny Armayanti; Luh Citrarasmi Dara Mestika; Ni Putu Citra Laksmi (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: Child development is a fundamental aspect determining their future quality of life. Stunting, as a long-term nutritional disorder, remains a significant health issue in Indonesia, with a prevalence of 30.8%, according to Riskesdas 2018. Developmental check-ups play a key role in detecting developmental deviations. Yet, parental involvement remains low and is closely related to the level of understanding and number of children they have. Method: his research employed a cross-sectional approach using a questionnaire on parental knowledge and participation in child development screening, involving 47 respondents. Results: Chi-square test results showed a significant correlation between knowledge level and parental participation (p=0.01), while parity was not significantly associated with parental involvement (p=0.60). Conclusion: The analysis results indicate a significant relationship between knowledge and parental participation in child developmental screening, whereas parity does not show a statistically significant relationship with parental involvement.